1996
DOI: 10.1021/la951541i
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of CdS and ZnS Particles in Nanophase Reactors Provided by Binary Liquids Adsorbed at Colloidal Silica Particles

Abstract: Determinations of adsorption excess isotherms of silica particle dispersions in ethanol−cyclohexane and in methanol−cyclohexane binary mixtures have established the formation of 0.5−5.0 nm thick alcohol rich adsorption layers at the silica particle interface. The adsorption layers on silica particles, formed in methanol−cyclohexane = 0.01:99.99 (mol/mol) and ethanol−cyclohexane = 0.05:99.95 (mol/mol), were used as nanophase reactors for the in situ generation of size-quantized CdS and ZnS particles. The semico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…It has been reported that many metal [17][18][19] and metal compound (oxides, sulfides, etc.) [20][21][22][23] nanoparticles have been deposited on MMT with some nanoparticles intercalated into its interlayers. These MMT-based catalysts combined the functions of the nanoparticles and MMT together, and exhibited synergetic effects [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that many metal [17][18][19] and metal compound (oxides, sulfides, etc.) [20][21][22][23] nanoparticles have been deposited on MMT with some nanoparticles intercalated into its interlayers. These MMT-based catalysts combined the functions of the nanoparticles and MMT together, and exhibited synergetic effects [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting subject to study is the liquid adsorption onto solid-liquid interfaces from binary liquids, however, its study has been limited mainly to the adsorption isotherm measurement and its model analysis in spite of its basic and technological importance [17][18][19]. Recently, we have succeeded in identifying the structure of ethanol adsorbed on a silica surface in cyclohexane by employing the combination of surface forces measurement, adsorption excess isotherm measurement and infrared spectroscopy in the attenuated total reflection mode (ATR-FTIR) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The preparations, purifications, and characterizations of hexadecyl pyridium modified montmorrilonite, HDP-M, and sodium dodecylbenzenesulfonate modified calumit, DBS-C, have been described (5)(6)(7)(8). Ethanol and cyclohexane (p.a., Reanal, Hungary) were dried over 0.4 nm molecular sieves (Merck AG, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…We have successfully employed ultrathin polar liquid layers, selectively adsorbed on solid surfaces in contact with alcohol-cyclohexane binary mixtures, as nanoreactors for the preparation of semiconductor particles (1,2). Specifically, we have generated CdS and ZnS nanoparticles in these nanoreactors at montmorrilonite clay platelet (5,6) and silica particle (7,8) surfaces.…”
Section: Introductionmentioning
confidence: 99%